Pengaruh Pertumbuhan Kredit Terhadap Profitabilitas dengan Tingkat Kolektibilitas Kredit Pada Lembaga Perkreditan Desa - Hariputri, Putu Utami; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2018)
This research is an empirical study which aims to know and test the effect of credit growth on profitability and credit collectability level in LPD. This research was conducted at LPD located in Denpasar in the period of 2014-2016 with total population of 35 LPD. The sampling technique used in this research is purposive sampling with criteria. This research uses 105 samples and analysis technique that is test of Moderated Regression Analysis with classical assumption test that is normality test, heterokedastisitas test, and autocorrelation test. Based on the results of the classical assumption test showed that the regression model used is correct. The result of research using moderation regression analysis showed that credit growth has a significant effect on profitability. The results show that increased credit growth is followed by increased profitability. The level of loan collectibility can moderate by weakening the negative effect of credit growth on profitabilit y.